2020
DOI: 10.1097/shk.0000000000001329
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Circulatory Support in Refractory Vasodilatory Septic Shock: a Randomized Controlled Porcine Study

Abstract: As controversy persists regarding the benefits of mechanical circulatory support in septic shock with a predominantly vasoplegic phenotype, preclinical studies may provide a useful alternative to fill the actual knowledge gap. Here, we investigated the physiologic responses to venoarterial extracorporeal membrane oxygenation therapy (VA-ECMO) in a clinically relevant porcine peritonitis-induced model of refractory vasodilatory septic shock. In 12 anesthetized, mechanically ventilated, and instrumented domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…However, the evidence of its benefits in adult patients is weak, particularly in cases of refractory septic shock 34). Controversies surrounding the benefits of ECMO in septic shock with a predominantly vasoplegic phenotype persist 35). Favorable outcomes of VA ECMO in patients with septic shock combined with heart failures have been reported for recent years 36)37)38)39)…”
Section: Indications Of Venoarterial Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…However, the evidence of its benefits in adult patients is weak, particularly in cases of refractory septic shock 34). Controversies surrounding the benefits of ECMO in septic shock with a predominantly vasoplegic phenotype persist 35). Favorable outcomes of VA ECMO in patients with septic shock combined with heart failures have been reported for recent years 36)37)38)39)…”
Section: Indications Of Venoarterial Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…Although these devices are used in the setting of cardiac and/or respiratory failure, and they increase circulatory blood flow (depending on configuration), they themselves do not reverse hypotension. 2 In fact, exposure to the nonbiological, non-endothelialized surfaces of the devices activates inflammatory pathways invoking a state mimicking the systemic inflammatory response syndrome thereby inducing hypotension. 13 There may be biological plausibility for increased response and favorable outcome to angiotensin II treatment in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 These devices may be deployed as a temporary intervention to bridge to recovery or transplantation, or as a form of durable support for the remainder of a patient's life. Although these devices restore circulatory blood flow, they do not reverse vasodilatory shock, 2 a common, yet devastating syndrome with death rates of 30% to 50% depending on the underlying etiology. 35 Attention to correcting underlying pathologies responsible for shock (eg, sepsis) is paramount to achieving a positive outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Data from studies involving septic patients receiving temporary MCS with ECMO show very high (64%‐93%) mortality rates 1 . A recent experimental study has further confirmed these clinical observations 2 . The Impella 5.0 is a temporary left ventricular assist device, which has shown favorable outcomes in terms of hemodynamic recovery in cardiogenic shock 3 .…”
Section: Figurementioning
confidence: 93%